Electrochemical Synthesis of Fe-doped TiO2 Nanotube for Gas Sensor Application - Faris, Mina Mohammed; Ayal, Asmaa Kadim (Iraqi Journal of Science, 2025)
Titanium dioxide (TiO2) nanotubes have gained particular interest as a material for gas sensors because of their vertical arrays, prepared by the anodization procedure. The presence of several oxygen vacancies in these nanotubes facilitates gas diffusion and provides additional active sites. This study examined the impact of voltages on the process of depositing iron nanoparticles onto arrays of TiO2 nanotubes (TNTs) for use as a gas sensor. The TNTs are manufactured using a straightforward and economical electrochemical anodization technique, specifically for gas sensor applications. By varying the deposition voltage (2-6 volts), ordered Fe-TNTs were efficiently manufactured using a simple two-step electrochemical process. It utilized energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), and field-emission scanning electron microscopy (FESEM) to study morphology, structure, and composition. Furthermore, gas sensor testing was implemented to examine the gas sensor’s response. An increase in the Fe doping voltage with TNTs altered the structure of the nanotubes, particularly at the highest voltages, according to XRD analysis. The best sensor for Fe-TNTs was made by doping Fe with TiO2 nanotubes at a doping voltage of 3 volts, depending on how well the gas sensitizers worked. The study demonstrated that using iron can increase TiO2’s efficiency as a gas sensor.